2018
DOI: 10.1371/journal.pone.0206464
|View full text |Cite
|
Sign up to set email alerts
|

Training with brain-machine interfaces, visuo-tactile feedback and assisted locomotion improves sensorimotor, visceral, and psychological signs in chronic paraplegic patients

Abstract: Spinal cord injury (SCI) induces severe deficiencies in sensory-motor and autonomic functions and has a significant negative impact on patients’ quality of life. There is currently no systematic rehabilitation technique assuring recovery of the neurological impairments caused by a complete SCI. Here, we report significant clinical improvement in a group of seven chronic SCI patients (six AIS A, one AIS B) following a 28-month, multi-step protocol that combined training with non-invasive brain-machine interface… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 83 publications
(105 reference statements)
2
41
0
Order By: Relevance
“…These efforts aimed at inducing activity-dependent plasticity 5 by the utilization of robotic trainers 68 , epidural electrical stimulation 911 , body-weight support trainers 12 , brain-machine interfaces 11,1315 , transcranial magnetic stimulation 16,17 and surface functional electrical stimulation (sFES) 18,19 . Recently, our group has shown that a training protocol (the Walk Again NeuroRehabilitation protocol (WANR)) 14,20 – induced a significant level of neurological recovery in a group of eight subjects with chronic complete paraplegia (seven AIS A, one AIS B), by combining assisted walk training with robotic walkers, electroencephalography (EEG)-based brain-machine interface (BMI), and continuous visuotactile feedback. Extending our previous findings, the present study describes our group’s effort to further enhance clinical neurological recovery in severe cases of SCI by providing more selective lower-limb musculoskeletal recruitment through sFES, while maintaining our fundamental philosophy of activating both ascending and descending neural pathways during the neurorehabilitation process.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These efforts aimed at inducing activity-dependent plasticity 5 by the utilization of robotic trainers 68 , epidural electrical stimulation 911 , body-weight support trainers 12 , brain-machine interfaces 11,1315 , transcranial magnetic stimulation 16,17 and surface functional electrical stimulation (sFES) 18,19 . Recently, our group has shown that a training protocol (the Walk Again NeuroRehabilitation protocol (WANR)) 14,20 – induced a significant level of neurological recovery in a group of eight subjects with chronic complete paraplegia (seven AIS A, one AIS B), by combining assisted walk training with robotic walkers, electroencephalography (EEG)-based brain-machine interface (BMI), and continuous visuotactile feedback. Extending our previous findings, the present study describes our group’s effort to further enhance clinical neurological recovery in severe cases of SCI by providing more selective lower-limb musculoskeletal recruitment through sFES, while maintaining our fundamental philosophy of activating both ascending and descending neural pathways during the neurorehabilitation process.…”
Section: Introductionmentioning
confidence: 99%
“…Extending our previous findings, the present study describes our group’s effort to further enhance clinical neurological recovery in severe cases of SCI by providing more selective lower-limb musculoskeletal recruitment through sFES, while maintaining our fundamental philosophy of activating both ascending and descending neural pathways during the neurorehabilitation process. As such, the BFNR (BMI, sFES, NeuroRehabilitation) protocol described here integrates four key elements to potentiate recovery in patients with SCI: muscle activation through sFES 2123 (see 24 for a review), balance control through body weight support 25 , real-time decoding of motor command (BMI) 14,20 and sensory feedback through a portable haptic device 26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another research group explored the use of EEG signals for the decoding of gait kinematics (Presacco et al, 2011;Nakagome et al, 2020), but not gait events. In our previous work (Tortora et al, 2020), we compared the results obtained with the EEG-driven LSTM network used in this study with respect to the methods proposed by Jorquera et al (2013) and Shokur et al (2018), that involved a similar classification problem, showing significantly better performance of our approach. On the other hand, a comparison of the performance of our hybrid approach with respect to other hybrid systems in literature is difficult since, as illustrated in the section 1.1, hybrid interfaces on lower limb applications are limited to classification scenarios that are very different from the one presented in this study.…”
Section: Discussionmentioning
confidence: 98%
“…This approach has been employed in numerous Brain Computer Interface (BCI) systems providing real-time communication and control. BCIs have been used to control devices such as a wheelchair (Carlson and del, 2013), prosthesis or functional electrical stimulator (FES) (Ramos-Murguialday et al, 2013), sometimes in combination with immersive feedback relating to rehabilitation (Shokur et al, 2018). Over the past several years, many publications have combined BCI, FES and other feedback devices to increase cortical plasticity in stroke survivors helping them regain movement control (Dobkin, 2007).…”
Section: Introductionmentioning
confidence: 99%